الإلتزام بالإعلام قبل التعاقد في ظل قانون حماية المستهلك - داهم, صبرين (جامعة الوادي University of Eloued, 2017)
إن حاجة الأفراد إلى السلع والخدمات تدفعهم إلى التعاقد مع المحترفين الذين إن يمتهنون بيع هذه السلع وآداء هذه الخدمات, سواء كانوا أشخاصا طبيعية أو معنوية, وتلك الحاجة وجدت مع وجود الإنسان, ولم تثر طبيعة العلاقة بين الطالب لتلك السلع والخدمات وبين المقدمين لها أية إهتمام, إلا مع ظهور التطور الصناعي الذي إعترى تلك العلاقة الإستهلاكية, ليكشف أنها علاقة غير متكافئة بطبيعتها حيث يظهر عمق إختصاص للمحترف ذاته, والكم الهائل من المعلومات الذي في حوزته, و ما يصادف ذلك الإمكانات المالية الضخمة التي بين يديه. من هنا برزت علاقة لأطراف غير متساوية. وهو ما أشار إليه بعض الفقه ورجال القانون حول وجود إختلال في التوازن التعاقدي في العلاقات بين المحترفين والمستهلكين, والذي مرده إلى عدم المساواة في الإعلام، ففي الوقت الذي يحيط فيه المحترف علما بالأموال والخدمات المعروضة في السوق، يبقى المستهلك في الغالب غير قادر على الإحاطة بها حتى يتسنى له بعد ذلك المقارنة بينها واختيار أحسنها جودة وأقلها سعرا، لذلك جاء الإعتراف بالحق في الإعلام مما أصبح إحدى الركائز الرئيسية لكل سياسة توضع للدفاع عن المستهلكين. The need for individuals to goods and services leads them to contract with professionals who are engaged in the sale of these goods and the performance of these services, whether natural or moral persons, and that need existed with the presence of human, did not raise the nature of the relationship between the student of those goods and services and the providers of any interest, But with the emergence of industrial development, which has seen this consumer relationship, to discover that it is a relationship is unequal nature, showing the depth of competence for the same professional, and the vast amount of information in his possession, and what coincides with the huge financial potential in his hands. Hence the relationship of unequal parties. This is what some jurisprudents and jurists have pointed out about the imbalance in the contractual balance in the relations between professionals and consumers, which is due to the inequality in the media. At a time when the professional takes note of the money and services offered in the market, the consumer is often unable to take care of them So that it can then compare them and choose the best quality and the lowest price, so the recognition of the right to the media, which has become one of the pillars of any policy to defend consumers.
قانون أعمال
Keywords: الإلتزام بالإعلام قبل التعاقد – المتدخل – حماية المستهلك; Commitment to information before contracting - Intervention - Consumer Protection